Answered

Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

solve the equation -2y + 6 =-12

Sagot :

Answer:

[tex] - 2y + 6 = - 12 \\ - 2y = - 12 - 6 \\ - 2y = - 18 \\ y = \frac{ - 18}{ - 2} \\ y = 9[/tex]

Answer:

-2y + 6 = -12 (subtract 6 from both sides to get the y-term alone)

-2y = -18 (divide both sides by -2 to get y alone)

y = 9 (this is your answer)